Have a nice day, be safe and healthy :)
Hope this helped
formula:
(a+b)^2
= a^2+2ab+b^2
Here, we have x^2 (as in a^2)
and -6x (as in 2ab), which, we're missing the b^2
(I'm not really sure how to describe this but bare with me)
-6/2 (-6 is from the -6x) = -3 (the b)
-3^2 = -3*-3 which is equal to 9 (positive 9)
Writing it out -
x^2-6x+9 = -5
- Addition of inequality -
Since we add 9 to the left side, we have to add 9 to the right side; which gives us:
x^2-6x+9=4
Next, lets put the x^2-6x+9 as in (a+b)^2:
(x-3)^2 = 4
Then let's do the square root of equality (square rooting both sides) :
x-3 = 2
Finally lets add 3 to both sides
x = 5
THE ANSWER IS x=5
Have a nice day, be safe + healthy - Hope this helped